2021
DOI: 10.1186/s13104-021-05794-3
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the sociodemographic and health conditions associated with self-rated wellbeing for Aboriginal and Torres Strait Islander adults

Abstract: Objective To identify sociodemographic factors and health conditions associated with self-rated wellbeing for Aboriginal and Torres Strait Islander adults. Participants were recruited via investigator networks and an online panel provider with an established nationwide panel of Aboriginal and Torres Strait Islander adults. Those interested were invited to complete a survey that included an assessment of wellbeing using a visual analogue scale. Data was collected from October–November 2019 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The present study provides evidence on the importance of holistic wellness among Indigenous youth. In regard to holistic wellness, many Indigenous people locate the concept of wellness within the Medicine Wheel, containing four balanced aspects of self: mental, physical, spiritual, and emotional [ 41 ]. The usability design preferences findings in the current study indicated the importance of the Medicine Wheel and balanced lifestyle in the images and words chosen by Indigenous adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study provides evidence on the importance of holistic wellness among Indigenous youth. In regard to holistic wellness, many Indigenous people locate the concept of wellness within the Medicine Wheel, containing four balanced aspects of self: mental, physical, spiritual, and emotional [ 41 ]. The usability design preferences findings in the current study indicated the importance of the Medicine Wheel and balanced lifestyle in the images and words chosen by Indigenous adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The usability design preferences findings in the current study indicated the importance of the Medicine Wheel and balanced lifestyle in the images and words chosen by Indigenous adolescents. Cultural identity and language are often identified as critical to wellness [ 41 ]. This is important, but also not surprising, given that Indigenous persona stories describe a world that is immersed in community and cultural activities where they use digital spaces and community events to ask for health advice from family.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations